Lightweight highlight cushioning material and preparation method thereof
By adding specific components to the EVA foaming material and optimizing the injection foaming process, the problem of premature decomposition of the foaming agent caused by excessive friction between the molten material and the injection barrel in the injection foaming process is solved, and the preparation of lightweight high light is achieved Highly efficient foaming and excellent mechanical properties of shock cushioning materials.
Patent Information
- Application Number
- CN202411800759.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-14
AI Technical Summary
In the injection foaming process of the existing EVA foaming material, the friction between the molten material and the inner wall of the injection gun barrel is too large, resulting in the premature decomposition of the foaming agent and reaction, which cannot achieve the expected foaming effect, and the product is prone to cracking and cannot meet the application. Require.
Based on ethylene-vinyl acetate copolymer, thermoplastic polyester elastomer, thermoplastic polyolefin elastomer, hydrogenated styrene-butadiene block copolymer and other components are added, and the fine component ratio control and injection foaming process is used. Optimize to reduce the friction between the molten material and the injection barrel and maintain the stability of the foaming agent.
The lightweight high-gloss cushioning material prepared in the injection foaming process has good high-gloss texture, good surface quality and excellent mechanical properties, and meets the product's rebound and cushioning performance requirements.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foaming materials, and in particular to a lightweight high-gloss shock-absorbing material and a preparation method thereof. Background Art
[0002] Ethylene-vinyl acetate copolymer (EVA) is a thermoplastic similar to rubber. Compared with polyethylene, it has excellent flexibility, low-temperature bending resistance, elasticity, stress cracking resistance, good plasticity and processability, so it is widely used. EVA has a wide range of applications. EVA foam material has the properties of softness, good elasticity, and chemical corrosion resistance. It is used in the soles and interior materials of mid-to-high-end tourist shoes, hiking shoes, slippers, and sandals.
[0003] The current EVA foam material generally adopts the compression foaming process. Compared with the injection foaming process, the compression foaming process is lower in cost and suitable for complex shapes, but the dimensional accuracy is limited, the surface quality is average, and the production efficiency is low. The injection foaming process has higher dimensional accuracy, faster cycle time and good surface quality, but in actual application, the current EVA foam material formula is often inferior to the product made by the compression foaming process when it is injection molded by the injection machine. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned defects or problems existing in the background technology and to provide a lightweight high-gloss shock-absorbing material and a preparation method thereof. The material can be prepared by an injection foaming process and has good product quality.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] Technical solution 1: A lightweight high-gloss shock-absorbing material, which includes the following components in parts by mass: 30-40 parts of ethylene-vinyl acetate copolymer; 15-25 parts of thermoplastic polyester elastomer; 12-18 parts of thermoplastic polyolefin elastomer; 20-25 parts of hydrogenated styrene-butadiene block copolymer; 4-8 parts of EPDM rubber; 7-10 parts of wear-resistant agent; 0.2-0.5 parts of active agent; 0.5-1 parts of auxiliary agent; 7-9 parts of high-gloss color particles; 0.5-1 parts of cross-linking agent; 5-8 parts of low-temperature foaming agent; wherein the Shore hardness range of the thermoplastic polyester elastomer is 60A-85A; the vinyl acetate content in the ethylene-vinyl acetate copolymer is 20%-30%.
[0007] Technical solution 2 based on technical solution 1: the thermoplastic polyester elastomer is a block copolymer type, which is composed of a hard segment and a soft segment, wherein the hard segment is polybutylene terephthalate, the soft segment is polytetramethylene ether glycol, and the mass fraction of the hard segment is 30%-45%, and the mass fraction of the soft segment is 55%-70%.
[0008] Technical solution three based on technical solution two: the hydrogenated styrene-butadiene block copolymer adopts a linear triblock copolymer with a molecular weight of 120,000 to 150,000.
[0009] Technical solution 4 based on technical solution 3: the wear-resistant agent adopts silicone wear-resistant agent.
[0010] Technical solution 5 based on technical solution 4: the active agent is one or two of stearic acid or fatty acid.
[0011] Technical solution six based on technical solution five: the high-gloss color particles are made of colored metallic pearlescent powder.
[0012] Technical solution seven based on technical solution six: the cross-linking agent is diisopropylbenzene peroxide.
[0013] Technical solution eight based on technical solution seven: the low-temperature foaming agent is white azodicarbonamide.
[0014] Technical solution nine based on technical solution eight: the auxiliary agent is zinc carbonate.
[0015] In addition, the present invention also provides technical solution ten: a method for preparing a lightweight high-gloss shock-absorbing material, which is based on the components of a lightweight high-gloss shock-absorbing material described in any one of technical solutions one to nine, and is prepared by the following steps: step one: weigh the other components except the auxiliary agent and the cross-linking agent according to the mass fraction, and mix them, the mixing temperature is 115±5°C, and the mixing time is 10-15min; step two: add the auxiliary agent and the cross-linking agent to the mixed product obtained in step one for further mixing, and the mixing temperature is 120 ±5℃, the mixing time is 10-15min; Step 3: Granulate the mixed product obtained in step 2, and add it to the injection molding machine to make the material in a molten state, and the four-section temperature of the injection barrel of the injection molding machine is 85℃, 90℃, 95℃, and 98℃; Step 4: Inject the molten material into the molding mold through the injection molding machine for foaming, the mold temperature of the molding mold is 175±5℃, and the foaming time is 4-8min; Step 5: Cool the molding mold, demould the material after it is shaped, and obtain the lightweight high-gloss shock-absorbing material.
[0016] It can be seen from the above description of the present invention that, compared with the prior art, the present invention has the following beneficial effects:
[0017] The inventor found that the quality of the obtained product was inferior to that of the product prepared by the molding process when the injection foaming process was used to carry out the foaming molding process of ethylene vinyl acetate copolymer. The reason is that in the current method of preparing foaming materials based on ethylene vinyl acetate copolymer as the basic component, the material is melted in the injection machine, and in the process of passing through the injection barrel of the injection machine, the friction between the molten material and the inner wall of the injection barrel of the injection machine is too large, resulting in the temperature of the molten material being higher than the preset range, so that the foaming agent in the molten material is decomposed and reacted prematurely, and then a large number of bubbles have appeared inside the molten material at the position of the injection barrel, but at this time there is not enough space and temperature to make the material completely foamed. After the molten material enters the inside of the molding mold, because the foaming agent has been consumed prematurely, the foaming effect of the material in the mold cannot meet the expected requirements. In addition, in this case, the product after demoulding is also prone to cracking at the thinner position due to the excessive foaming ratio, resulting in the product being unusable. Therefore, the current foaming material formula based on ethylene vinyl acetate copolymer, the product obtained by the injection foaming process, cannot meet the requirements.
[0018] At the same time, the present invention provides a lightweight high-gloss shock-absorbing material, in which high-gloss color particles are added to the formula, and the high-gloss texture of the product is achieved through the high-gloss color particles. At the same time, the use of a low-temperature foaming agent can reduce the influence of the color of the foaming agent on the final material, so that the color of the high-gloss color particles can be highlighted on the surface of the material. At the same time, foaming at a low temperature can reduce the agglomeration of the high-gloss color particles in the system, and the high-gloss color particles have better dispersion in the system, which can form a more uniform high-gloss texture. The use of a low-temperature foaming agent will cause the molten material to be easier to decompose and react in the ejection barrel. Therefore, it is necessary to further reduce the friction of the molten material in the ejection barrel.
[0019] However, reducing the friction of the molten material in the injection barrel, that is, increasing the fluidity of the molten material in the injection barrel, will lead to reduced molding accuracy and poor surface quality of the product, and will also lead to reduced mechanical properties of the product, which will fail to meet the required rebound and shock-absorbing performance requirements.
[0020] The present invention provides a light-weight high-gloss shock-absorbing material, the formula of which can be used to prepare a foamed material through an injection foaming process, and the prepared product has good high-gloss texture, good surface quality and excellent mechanical properties. In the formula, ethylene vinyl acetate copolymer is a basic material, and thermoplastic polyester elastomer, thermoplastic polyolefin elastomer, hydrogenated styrene-butadiene block copolymer and ethylene propylene diene monomer rubber are added to the basic material.
[0021] Among them, the thermoplastic polyester elastomer is a block copolymer type, composed of hard segment polybutylene terephthalate and soft segment polytetramethylene glycol. Its Shore hardness range is precisely controlled at 60A-85A, and the mass fractions of the hard segment and the soft segment are limited. This unique structure and hardness range give the material just the right flexibility and toughness. When the material flows through the ejection barrel, it can effectively buffer the impact force between the material and the tube wall, reduce the friction coefficient, avoid abnormal temperature increase of the material due to friction, maintain the stability of the foaming agent, and prevent premature decomposition. Thermoplastic polyolefin elastomer has excellent fluidity control ability. Its addition amount is maintained at 12-18 parts. It will not cause the material to be too thin and soft and difficult to form due to excessive addition, and it can cooperate with other components to keep the molten material in a smooth flow state in the ejection barrel. When the material faces pressure and resistance in the barrel, it can evenly disperse the stress, ensure that the material moves forward at a uniform speed, and avoid the problem of uneven foaming caused by fast and slow flow rate. Hydrogenated styrene-butadiene block copolymer uses a linear triblock copolymer with a molecular weight of 120,000 to 150,000. With its specific molecular structure and molecular weight, it greatly optimizes the overall rheological properties of the material. In the injection foaming process, it acts like a "lubricant", allowing the material to slide smoothly against the inner wall of the injection barrel, reducing the phenomenon of jamming and frictional heat generation, ensuring that the foaming agent can play a role at the right time and temperature conditions, and accurately achieve the expected foaming ratio. Through the coordination of thermoplastic polyester elastomer, thermoplastic polyolefin elastomer, and hydrogenated styrene-butadiene block copolymer and the control of the mass fraction of each component, the molten material has good fluidity in the injection barrel, reducing the friction between the molten material and the injection barrel, reducing the premature decomposition and reaction of the foaming agent in the injection barrel, and at the same time ensuring that the product has good mechanical properties, and the rebound and shock absorbing properties of the obtained foaming material can meet the requirements.
[0022] EPDM rubber not only enhances the durability of the product after it is made from the material and withstands various harsh environments, but also in the injection foaming process, due to its good flexibility and elastic recovery ability, it can absorb part of the vibration generated by the flow of the material, further reduce the friction noise and wear between the material and the injection barrel, and maintain the structural integrity of the material.
[0023] The anti-wear agent uses silicone anti-wear agent, which not only reduces the friction between the material and the injection barrel, but also gives the material additional anti-wear properties. As the material passes through the injection barrel again and again, the fine protective film formed by the silicone anti-wear agent can effectively resist the scratches on the tube wall, prevent the debris generated by friction from mixing into the material, maintain the purity of the material, ensure the uniformity of the internal structure of the product, and improve the mechanical properties and surface smoothness of the product.
[0024] The surfactant uses one or two of stearic acid or fatty acid to accurately adjust the interfacial tension between the components, promote the efficient fusion of the components during the mixing and melting process, and make the material texture uniform and fine. In this way, when the material flows in the shooting barrel, the local resistance will not increase due to the mutual repulsion and agglomeration of the internal components, which ensures the smooth passage of the material in all directions and maintains a stable processing state.
[0025] The high-gloss color particles are made of colored metallic pearlescent powder, which not only gives the product a high-gloss texture and meets the aesthetic needs of the appearance, but also benefits from the synergistic effect of the low-temperature foaming agent. In a low-temperature environment, the metallic pearlescent powder can be evenly dispersed in the material system to avoid agglomeration and sedimentation due to high temperature, ensuring that the product has bright color and a long-lasting high-gloss effect.
[0026] The cross-linking agent uses dicumyl peroxide to build a cross-linking network inside the material, giving the product appropriate strength and elasticity. During the injection foaming process, the stable cross-linking structure can resist the pulling force generated by the high-speed flow of the material, prevent the material from deforming and breaking, maintain the product's dimensional accuracy, and improve the product's comprehensive mechanical properties.
[0027] The low-temperature foaming agent uses white azodicarbonamide, which cleverly utilizes its low-temperature decomposition characteristics to reduce the interference of the foaming process on the color of the high-gloss color particles, while avoiding the disadvantages of excessive foaming and uncontrolled foaming of materials caused by high temperature. With the precise control of process parameters, the foaming process is smooth and orderly, and the foaming ratio and density distribution of the product are accurately controlled.
[0028] Zinc carbonate is used as an additive, which plays a key role in stabilizing the chemical properties of materials and fine-tuning processing performance. In the entire process of material mixing, injection, foaming, etc., zinc carbonate escorts the whole process, timely neutralizes the acidic substances that may be generated inside the material, maintains the pH balance of the material, and prevents the chemical property fluctuations of the material from affecting the foaming effect and the final performance of the product.
[0029] In addition, the present invention also provides a corresponding preparation method, first accurately weigh the other components except the auxiliary agent and the cross-linking agent to allow the components to be initially fused; then add the auxiliary agent and the cross-linking agent for secondary mixing to compact the internal structure of the material; granulate the mixed product and put it into the injection molding machine, and set the temperature according to the four stages of 85°C, 90°C, 95°C, and 98°C to keep the material in an ideal molten state; then inject it into the molding mold, control the foaming time, and promote efficient and orderly foaming; finally cool and shape, demold, and obtain a lightweight high-gloss cushioning material product with high-gloss texture, high-quality surface and excellent mechanical properties. Through this complete set of material formulas and preparation processes, many existing problems in the injection foaming process have been successfully overcome, and the market's stringent demand for high-performance cushioning materials has been effectively met. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are preferred embodiments of the present invention and should not be regarded as excluding other embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In the claims and description of the present invention, if the terms "include", "have" and their variations are used, they are intended to mean "including but not limited to".
[0032] The invention provides a lightweight high-gloss shock-absorbing material, which includes the following components in parts by mass: 30-40 parts of ethylene-vinyl acetate copolymer; 15-25 parts of thermoplastic polyester elastomer; 12-18 parts of thermoplastic polyolefin elastomer; 20-25 parts of hydrogenated styrene-butadiene block copolymer; 4-8 parts of EPDM rubber; 7-10 parts of wear-resistant agent; 0.2-0.5 parts of active agent; 0.5-1 parts of auxiliary agent; 7-9 parts of high-gloss color particles; 0.5-1 parts of cross-linking agent; 5-8 parts of low-temperature foaming agent; wherein the Shore hardness range of the thermoplastic polyester elastomer is 60A-85A; the vinyl acetate content in the ethylene-vinyl acetate copolymer is 20%-30%.
[0033] Among them, the mass content of vinyl acetate in the adopted ethylene-vinyl acetate copolymer is 20%-30%, and the appropriate EVA model can be selected according to the content requirement; VA is a flexible segment in the EVA molecular chain, and the internal rotation of the chemical bonds in the molecule is freer, which can form an irregularly curled random coil conformation. The appropriate VA mass content range can ensure the uniform distribution of the random coil conformation in the tertiary structure of the polymer, effectively reduce the crystallization ability of the ethylene segment in the polymer, and keep the polymer molecular chain as flexible as possible, so that the molten material has good fluidity, and can also ensure the softness and high elasticity of the composite material.
[0034] The thermoplastic polyester elastomer is a block copolymer type, which is composed of a hard segment and a soft segment, wherein the hard segment is polybutylene terephthalate and the soft segment is polytetramethylene ether glycol. Its Shore hardness range is precisely controlled at 60A-85A, and the mass fraction of the hard segment is 30%-45%, and the mass fraction of the soft segment is 55%-70%. This unique structure and hardness range give the material just the right flexibility and toughness. When the material flows through the ejection barrel, it can effectively buffer the impact force between the material and the tube wall, reduce the friction coefficient, avoid abnormal temperature increase of the material due to friction, maintain the stability of the foaming agent, and prevent premature decomposition. The thermoplastic polyester elastomer used in the lightweight high-gloss shock-absorbing material can be a conventional product available on the market.
[0035] Thermoplastic polyolefin elastomer has excellent fluidity control ability. The addition amount is maintained at 12-18 parts. It will not cause the material to be too thin and soft and difficult to form due to excessive amount. It can also cooperate with other components to keep the molten material flowing smoothly in the injection barrel. When the material faces pressure and resistance in the barrel, it can evenly disperse the stress to ensure that the material moves forward at a uniform speed and avoid the problem of uneven foaming caused by the flow rate being fast or slow. The model of the thermoplastic polyolefin elastomer used in the lightweight high-gloss shock-absorbing material can be one or more of the models Engage8450, Engage8003, Engage7467, Engage8150 and Engage8180.
[0036] The hydrogenated styrene-butadiene block copolymer adopts a linear triblock copolymer with a molecular weight of 120,000 to 150,000. With its specific molecular structure and molecular weight, the overall rheological properties of the material are optimized to a great extent. In the injection foaming process, it is like a "lubricant", allowing the material to slide smoothly against the inner wall of the injection barrel, reducing the phenomenon of jamming and frictional heat generation, ensuring that the foaming agent can play a role at the right time and temperature conditions, and accurately achieve the expected foaming ratio. The hydrogenated styrene-butadiene block copolymer used in the lightweight high-gloss shock-absorbing material can be a conventional commercially available product.
[0037] By combining thermoplastic polyester elastomer, thermoplastic polyolefin elastomer and hydrogenated styrene-butadiene block copolymer and controlling the mass fraction of each component, the molten material has better fluidity in the ejection barrel, the friction between the molten material and the ejection barrel is reduced, and the premature decomposition and reaction of the foaming agent in the ejection barrel is reduced. At the same time, it is ensured that the product has good mechanical properties, and the rebound and shock-absorbing properties of the obtained foaming material can meet the requirements.
[0038] In addition, in the above formula, EPDM rubber not only enhances the durability of the product after being made into the material and withstands various harsh environments, but also in the injection foaming process, due to its good flexibility and elastic recovery ability, it can absorb part of the vibration generated by the flow of materials, further reduce the friction noise and wear between the material and the injection barrel, and maintain the structural integrity of the material.
[0039] The anti-wear agent uses silicone anti-wear agent, which not only reduces the friction between the material and the injection barrel, but also gives the material additional anti-wear properties. As the material passes through the injection barrel again and again, the fine protective film formed by the silicone anti-wear agent can effectively resist the scratches on the tube wall, prevent the debris generated by friction from mixing into the material, maintain the purity of the material, ensure the uniformity of the internal structure of the product, and improve the mechanical properties and surface smoothness of the product.
[0040] The surfactant uses one or two of stearic acid or fatty acid to accurately adjust the interfacial tension between the components, promote the efficient fusion of the components during the mixing and melting process, and make the material texture uniform and fine. In this way, when the material flows in the shooting barrel, the local resistance will not increase due to the mutual repulsion and agglomeration of the internal components, which ensures the smooth passage of the material in all directions and maintains a stable processing state.
[0041] The high-gloss color particles are made of colored metallic pearlescent powder, which not only gives the product a high-gloss texture and meets the aesthetic needs of the appearance, but also benefits from the synergistic effect of the low-temperature foaming agent. In a low-temperature environment, the metallic pearlescent powder can be evenly dispersed in the material system to avoid agglomeration and sedimentation due to high temperature, ensuring that the product has bright color and a long-lasting high-gloss effect.
[0042] The cross-linking agent uses dicumyl peroxide to build a cross-linking network inside the material, giving the product appropriate strength and elasticity. During the injection foaming process, the stable cross-linking structure can resist the pulling force generated by the high-speed flow of the material, prevent the material from deforming and breaking, maintain the product's dimensional accuracy, and improve the product's comprehensive mechanical properties.
[0043] The low-temperature foaming agent uses white azodicarbonamide, which cleverly utilizes its low-temperature decomposition characteristics to reduce the interference of the foaming process on the color of the high-gloss color particles, while avoiding the disadvantages of excessive foaming and uncontrolled foaming of materials caused by high temperature. With the precise control of process parameters, the foaming process is smooth and orderly, and the foaming ratio and density distribution of the product are accurately controlled.
[0044] Zinc carbonate is used as an additive, which plays a key role in stabilizing the chemical properties of materials and fine-tuning processing performance. In the entire process of material mixing, injection, foaming, etc., zinc carbonate escorts the whole process, timely neutralizes the acidic substances that may be generated inside the material, maintains the pH balance of the material, and prevents the chemical property fluctuations of the material from affecting the foaming effect and the final performance of the product.
[0045] In addition, the present invention specification also provides a method for preparing the above-mentioned lightweight high-gloss shock-absorbing material. The method is based on the components of the above-mentioned lightweight high-gloss shock-absorbing material and is prepared by the following steps:
[0046] Step 1: Weigh the other components except the auxiliary agent and the cross-linking agent according to the mass fraction, and mix them at a mixing temperature of 115±5℃ for 10-15min;
[0047] Step 2: Add the auxiliary agent and the cross-linking agent to the mixed product obtained in step 1 for further mixing, the mixing temperature is 120±5°C, and the mixing time is 10-15min;
[0048] Step 3: Granulate the mixed product obtained in step 2, and add it to the injection molding machine to make the material in a molten state. The temperature of the four sections of the injection barrel of the injection molding machine is 85° C., 90° C., 95° C., and 98° C.;
[0049] Step 4: Inject the molten material into the molding mold through the injection machine for foaming. The mold temperature of the molding mold is 175±5℃ and the foaming time is 4-8min.
[0050] Step 5: Cool the molding mold, and demould the material after it is shaped to obtain the lightweight high-gloss shock-absorbing material.
[0051] The preparation method of the above-mentioned lightweight high-gloss cushioning material first accurately weighs the other components except the auxiliary agent and the cross-linking agent to allow the components to initially blend; then add the auxiliary agent and the cross-linking agent for secondary mixing to compact the internal structure of the material; the mixed product is granulated and put into the injection molding machine, and the material is maintained in an ideal molten state according to the four-stage temperature setting of 85°C, 90°C, 95°C, and 98°C; then it is injected into the molding mold to control the foaming time to promote efficient and orderly foaming; finally, it is cooled, shaped, and demolded to obtain a lightweight high-gloss cushioning material product with high-gloss texture, high-quality surface and excellent mechanical properties. Through this complete set of material formulas and preparation processes, many existing problems in the injection foaming process have been successfully overcome, and the market's stringent demand for high-performance cushioning materials has been effectively met.
[0052] To further illustrate the technical effects of the formula of the lightweight high-gloss shock-absorbing material and the preparation method thereof provided by the present invention, the embodiments of the present invention provide the following examples and comparative examples.
[0053] Example 1
[0054] The lightweight high-gloss shock-absorbing material provided in Example 1 includes the following components in parts by mass:
[0055] 30 parts of ethylene-vinyl acetate copolymer; 15 parts of thermoplastic polyester elastomer; 12 parts of thermoplastic polyolefin elastomer; 20 parts of hydrogenated styrene-butadiene block copolymer; 4 parts of EPDM rubber; 7 parts of wear-resistant agent; 0.2 parts of active agent; 0.5 parts of auxiliary agent; 7 parts of high-gloss color particles; 0.5 parts of cross-linking agent; 5 parts of low-temperature foaming agent.
[0056] Among them, the vinyl acetate content in the ethylene-vinyl acetate copolymer is 20%; the mass proportion of the hard segment in the thermoplastic polyester elastomer is 30%, the proportion of the soft segment is 70%, and the Shore hardness is 60A. The hydrogenated styrene-butadiene block copolymer adopts a linear triblock copolymer with a molecular weight of about 120,000. The wear-resistant agent adopts an organic silicon wear-resistant agent. The active agent adopts stearic acid. The high-gloss color particles adopt white metallic pearlescent powder. The cross-linking agent adopts diisopropylbenzene peroxide. The low-temperature foaming agent adopts white azodicarbonamide. The auxiliary agent adopts zinc carbonate. The above components are all commercially available materials.
[0057] Based on the above components, the following preparation method is used:
[0058] Step 1: Weigh the other components except the auxiliary agent and the cross-linking agent according to the mass fraction, and mix them at a mixing temperature of 115±5℃ for 10min;
[0059] Step 2: Add the auxiliary agent and the cross-linking agent to the mixed product obtained in step 1 for further mixing, the mixing temperature is 120±5°C, and the mixing time is 10 minutes;
[0060] Step 3: Granulate the mixed product obtained in step 2, and add it to the injection molding machine to make the material in a molten state. The temperature of the four sections of the injection barrel of the injection molding machine is 85° C., 90° C., 95° C., and 98° C.;
[0061] Step 4: Inject the molten material into the molding mold through the injection machine for foaming. The mold temperature of the molding mold is 175±5℃ and the foaming time is 4min.
[0062] Step 5: Cool the molding mold, and demould the material after it is shaped to obtain the lightweight high-gloss shock-absorbing material.
[0063] Example 2
[0064] 35 parts of ethylene-vinyl acetate copolymer; 20 parts of thermoplastic polyester elastomer; 15 parts of thermoplastic polyolefin elastomer; 22.5 parts of hydrogenated styrene-butadiene block copolymer; 6 parts of EPDM rubber; 8.5 parts of wear-resistant agent; 0.35 parts of active agent; 0.75 parts of auxiliary agent; 8 parts of high-gloss color particles; 0.75 parts of cross-linking agent; 6.5 parts of low-temperature foaming agent.
[0065] Among them, the vinyl acetate content in the ethylene-vinyl acetate copolymer is 26%; the mass proportion of the hard segment in the thermoplastic polyester elastomer is 40%, the proportion of the soft segment is 60%, and the Shore hardness is 68A. The hydrogenated styrene-butadiene block copolymer adopts a linear triblock copolymer with a molecular weight of about 150,000. The wear-resistant agent adopts an organic silicon wear-resistant agent. The active agent adopts stearic acid. The high-gloss color particles adopt white metallic pearlescent powder. The cross-linking agent adopts diisopropylbenzene peroxide. The low-temperature foaming agent adopts white azodicarbonamide. The auxiliary agent adopts zinc carbonate. The above components are all commercially available materials.
[0066] Based on the above components, the following preparation method is used:
[0067] Step 1: Weigh the other components except the auxiliary agent and the cross-linking agent according to the mass fraction, and mix them at a mixing temperature of 115±5℃ for 15min;
[0068] Step 2: Add the auxiliary agent and the cross-linking agent to the mixed product obtained in step 1 for further mixing, the mixing temperature is 120±5°C, and the mixing time is 15 minutes;
[0069] Step 3: Granulate the mixed product obtained in step 2, and add it to the injection molding machine to make the material in a molten state. The temperature of the four sections of the injection barrel of the injection molding machine is 85° C., 90° C., 95° C., and 98° C.;
[0070] Step 4: Inject the molten material into the molding mold through the injection machine for foaming. The mold temperature of the molding mold is 175±5℃ and the foaming time is 8min.
[0071] Step 5: Cool the molding mold, and demould the material after it is shaped to obtain the lightweight high-gloss shock-absorbing material.
[0072] Example 3
[0073] 40 parts of ethylene-vinyl acetate copolymer; 25 parts of thermoplastic polyester elastomer; 18 parts of thermoplastic polyolefin elastomer; 25 parts of hydrogenated styrene-butadiene block copolymer; 8 parts of EPDM rubber; 10 parts of wear-resistant agent; 0.5 parts of active agent; 1 part of auxiliary agent; 9 parts of high-gloss color particles; 1 part of cross-linking agent; 8 parts of low-temperature foaming agent.
[0074] Among them, the vinyl acetate content in the ethylene-vinyl acetate copolymer is 30%; the mass proportion of the hard segment in the thermoplastic polyester elastomer is 45%, the proportion of the soft segment is 55%, and the Shore hardness is 75A. The hydrogenated styrene-butadiene block copolymer adopts a linear triblock copolymer with a molecular weight of about 150,000. The wear-resistant agent adopts an organic silicon wear-resistant agent. The active agent adopts stearic acid. The high-gloss color particles adopt white metallic pearlescent powder. The cross-linking agent adopts diisopropylbenzene peroxide. The low-temperature foaming agent adopts white azodicarbonamide. The auxiliary agent adopts zinc carbonate. The above components are all commercially available materials.
[0075] Comparative Example 1
[0076] Based on Example 2, the difference from Example 2 is that no thermoplastic polyester elastomer is added to the formula.
[0077] Comparative Example 2
[0078] Based on Example 2, the difference from Example 2 is that no thermoplastic polyester elastomer and hydrogenated styrene-butadiene block copolymer are added to the formula.
[0079] Comparative Example 3
[0080] Based on Example 2, the difference from Example 2 is that no thermoplastic polyester elastomer, thermoplastic polyolefin elastomer, or hydrogenated styrene-butadiene block copolymer is added to the formula.
[0081] Comparative Example 4
[0082] Based on Example 2, the difference between it and Example 2 is that the Shore hardness of the thermoplastic polyester elastomer used in the formula is 40A.
[0083] Comparative Example 5
[0084] Based on Example 2, the difference between it and Example 2 is that the Shore hardness of the thermoplastic polyester elastomer used in the formula is 90A.
[0085] The physical properties and appearance of the above-mentioned Examples 1-3 and Comparative Examples 1-5 were tested, wherein the test standard for the shock absorption G value was the national standard J4004. The test results are as follows:
[0086]
[0087] It is easy to know from the above test results that in the formula of the lightweight high-gloss shock-absorbing material provided by the present invention, the thermoplastic polyester elastomer, the thermoplastic polyolefin elastomer, the hydrogenated styrene-butadiene block copolymer and other components work together to affect the performance and appearance of the material. Among them, components such as thermoplastic polyester elastomer, hydrogenated styrene-butadiene block copolymer and thermoplastic polyolefin elastomer play an important role in maintaining the fluidity of the material, reducing friction, improving mechanical properties and ensuring the appearance quality. In addition, the hardness of the thermoplastic polyester elastomer needs to be controlled within an appropriate range in order for the material to achieve optimal performance. Too hard or too soft will have an adverse effect on product performance.
[0088] The description of the above specification and embodiments is used to explain the protection scope of the present invention, but does not constitute a limitation on the protection scope of the present invention. Through the enlightenment of the present invention or the above embodiments, ordinary technicians in this field can obtain modifications, equivalent substitutions or other improvements to the embodiments of the present invention or part of the technical features thereof through logical analysis, reasoning or limited experiments, which should be included in the protection scope of the present invention.
Claims
1. A lightweight high-gloss shock-absorbing material, characterized in that: The composition includes the following components in parts by weight: 30-40 parts of ethylene-vinyl acetate copolymer; 15-25 parts of thermoplastic polyester elastomer; 12-18 parts of thermoplastic polyolefin elastomer; 20-25 parts of hydrogenated styrene-butadiene block copolymer; 4-8 parts of EPDM rubber; 7-10 parts of anti-wear agent; 0.2-0.5 parts of active agent; 0.5-1 parts of auxiliary agent; 7-9 parts of high-gloss color particles; 0.5-1 parts of cross-linking agent; 5-8 parts of low-temperature foaming agent; The Shore hardness of the thermoplastic polyester elastomer is in the range of 60A-75A; the vinyl acetate content in the ethylene-vinyl acetate copolymer is 20%-30%.
2. A lightweight high-gloss shock-absorbing material as claimed in claim 1, characterized in that: The thermoplastic polyester elastomer is a block copolymer type, which consists of a hard segment and a soft segment, wherein the hard segment is polybutylene terephthalate, the soft segment is polytetramethylene ether glycol, and the mass fraction of the hard segment is 30%-45%, and the mass fraction of the soft segment is 55%-70%.
3. A lightweight high-gloss shock-absorbing material as claimed in claim 2, characterized in that: The hydrogenated styrene-butadiene block copolymer is a linear triblock copolymer with a molecular weight of 120,000 to 150,000.
4. A lightweight high-gloss shock-absorbing material as claimed in claim 3, characterized in that: The anti-wear agent is an organic silicon anti-wear agent.
5. A lightweight high-gloss shock-absorbing material as claimed in claim 4, characterized in that: The active agent is one or both of stearic acid and fatty acid.
6. A lightweight high-gloss shock-absorbing material as claimed in claim 5, characterized in that: The high-gloss color particles are made of colorful metallic pearl powder.
7. A lightweight high-gloss shock-absorbing material as claimed in claim 6, characterized in that: The cross-linking agent is dicumyl peroxide.
8. The lightweight high-gloss shock-absorbing material according to claim 7, characterized in that: The low-temperature foaming agent is white azodicarbonamide.
9. A lightweight high-gloss shock-absorbing material as claimed in claim 8, characterized in that: The auxiliary agent is zinc carbonate.
10. A method for preparing a lightweight high-gloss shock-absorbing material, characterized in that: A component of a lightweight high-gloss shock-absorbing material according to any one of claims 1 to 9 is prepared by the following steps: Step 1: Weigh the other components except the auxiliary agent and the cross-linking agent according to the mass fraction, and mix them at a mixing temperature of 115±5℃ for 10-15min; Step 2: Add the auxiliary agent and the cross-linking agent to the mixed product obtained in step 1 for further mixing, the mixing temperature is 120±5°C, and the mixing time is 10-15min; Step 3: Granulate the mixed product obtained in step 2, and add it to the injection molding machine to make the material in a molten state. The temperature of the four sections of the injection barrel of the injection molding machine is 85° C., 90° C., 95° C., and 98° C.; Step 4: The molten material is injected into the molding mold by the injection machine for foaming. The mold temperature of the molding mold is 175±5℃. Foaming time is 4-8min; Step 5: Cool the molding mold, and demould the material after it is shaped to obtain the lightweight high-gloss shock-absorbing material.
Citation Information
Cited By
Light PU (polyurethane) foamed sole and preparation method thereof
CN119978606A
TPR foaming material and preparation method thereof
CN120590716A